ON A SPECTRAL PROBLEM FOR A SYSTEM OF PARTIAL DIFFERENTIAL EQUATIONS - Harutunyan, T. N.; Sahakyan, G. H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2005)
The accounting of the eigenvalues and the completeness of the eigenfunctions has been proved for a boundary problem with partial derivatives.